Comparative Study for Understanding the Spatial Growth Pattern of Pune and Jaipur City from 1990 to 2020 - Lohiya, Puja Rouhit; Sheladiya, Kaushikkumar Prafulbhai; Patel, Chetan R (Geoplanning: Journal of Geomatics and Planning, 2023)
Understanding the urban form, conducting spatial change analysis of an urban area using time-series data, and identifying urban growth drivers play a crucial part in framing policies for sustainable planning practices. In this research, an inverse S-curve function is employed to examine Urban Land Densities (ULD) derived from concentric divisions of urban regions in Pune and Jaipur. The inverse S-curve quantitatively describes variations in Urban Land Density (ULD) from the urban center to the outskirts. Consequently, the parameters identified during the curve-fitting process offer information about the urban form of the cities, shedding light on their rate of expansion, level of compactness, and the nature of sprawl. Built-up area is determined from the Landsat datasets for the years 1991, 1996, 2001, 2006, 2011,2016, and 2021. The analysis confirmed that Pune revealed an increase in sprawling, expansive, and low-density development. As a city that has grown linearly, Jaipur has experienced more constrained growth than Pune. Additionally, the fitted ULD equation provided an accurately fitted radius for Jaipur, but not for Pune, highlighting the equation's shortcomings. The direction analysis and understanding of the change in the slopes of the S curve further led to identifying growth drivers, broadly classified into proximity, government intervention, socioeconomic, and physical factors. The study can help achieve future research objectives in simulating and modeling urban growth and creating policies to deal with related problems.